Cytogenetic Effects of Magnesium Sulphate on The Root Tip Cells of Pea (Pisum sativum L.cv.araka) - AYAZ, EMINE; NAMLI, SUREYYA (Asian Journal of Chemistry, 2010)
The effects of magnesium sulphate on mitosis were investigated in Pisum sativum L.cv.araka. developed in vitro conditions. The roots of pea (Pisum sativum L.cv.araka) were treated with MgSO4 concentrations of 1 -0.1 -0.01 mg/L for 3-6 and 12 h treatment periods. It was found that MgSO4 has a marked mitodepressive action on mitosis. Magnesium sulphate significantly decreased the mitotic index at all concentrations and treatment periods. Mitotic abnormalities were increased and the mitotic index was decreased depending on the concentration and duration time of magnesium sulphate applied.